Optimization of Bamboo Chicken Processing - Azad , S.A.K; Mallika, E.Naga; Rao, B. Eswara; Babu, A. Jagadeesh; Veena , D. (Journal of Meat Science, 2014)
Bamboo chicken is a traditional low fat meat product of coastal Andhra Pradesh. Processing method was standardized and product was prepared with both traditional bamboo and locally available bamboo. The products were analyzed for physico-chemical (pH and proximate composition) and sensory attributes. No significant different in pH, moisture and fat content and sensory attributes between the treated formulation and the control product was observed. The finished product is dry due to draining out of the fluid present in the bamboo chicken after cooking.